Peran Pesantren dalam Dunia Usaha - Junaedi Junaedi (LP3M INSTITUT KH YAZID KARIMULLAH, 2022)
Historically, the existence of Islamic boarding schools began to receive full attention from the government after the issuance of Law (UU) Pesantren No. 18 of 2019. Which regulates the implementation of the education function, the function of da'wah and the function of community empowerment. With the issuance of this law, it is a breath of fresh air for the role of Islamic boarding schools in providing educational services, building and maintaining the Unitary State of the Republic of Indonesia as a field of da'wah in maintaining the traditions and teachings of Islam rahmatan lil'alamin. Islamic boarding schools under individual policies led by a figure (kyai, Habib, ust and others) organize and formulate education optimally in accordance with the characteristics and peculiarities of the pesantren, not only educating, teaching, preaching, and training students according to Islamic rules. However, Islamic boarding schools are required to be independent, one of the efforts to encourage this independence is through the establishment of the Pesantren Business World. With the existence of this pesantren-owned business, students are prepared to enter the community by bringing religious knowledge and general knowledge, so they are not rigid in entering the world of business, business, culture and others. Pesantren besides being a means of da'wah with a deepening culture of Islam, however, it does not have to be hands off with the business world to realize business innovation as a driving force for the economy of pesantren and the people.